Bob the Builder. The three musketrucks - Morrissey, Neil.; Rackstraw, Rob.; Harbour, Kate.; Chapman, Keith; HIT Entertainment; HOT Animation (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2008)
Join the Three Musketrucks: Packer, Scambler and the newest member of the Can-Do Crew, Dodger, in Bob the Builder's newest building adventures!
Dodger the Milktruck -- The three musketrucks -- Dodger's dairy disaster -- Scrambler the goat herder -- Packer's big delivery.
Title from container.
Based on the characters created by Keith Chapman.
Originally broadcast on television in 2007.
Special features: "Fireman Sam joker soaker" bonus episode (English & dubbed French); "Fifi & the flowertots: spotty pip (with vegetables interstitial)" bonus episode; meet 3 new memebers of the Can-Do Crew: Packer, Dodger and Tumbler.
Voices: Neil Morrissey, Rob Rackstraw, Kate Harbour.
Not rated.
Keywords: Bob the Builder (Fictitious character) -- Juvenile drama; Construction equipment -- Juvenile drama; Friendship -- Juvenile drama; Cooperation -- Juvenile drama; Television programs for children; Animated television programs